Toward biomass-derived renewable plastics: Production of 2,5-furandicarboxylic acid from fructose - Motagamwala, Ali Hussain (Sci Adv, 2018)
We report a process for converting fructose, at a high concentration (15 weight %), to 2,5-furandicarboxylic acid (FDCA), a monomer used in the production of polyethylene furanoate, a renewable plastic. In our process, fructose is dehydrated to hydroxymethylfurfural (HMF) at high yields (70%) using a γ-valerolactone (GVL)/H(2)O solvent system. HMF is subsequently oxidized to FDCA over a Pt/C catalyst with 93% yield. The advantage of our system is the higher solubility of FDCA in GVL/H(2)O, which allows oxidation at high concentrations using a heterogeneous catalyst that eliminates the need for a homogeneous base. In addition, FDCA can be separated from the GVL/H(2)O solvent system by crystallization to obtain >99% pure FDCA. Our process eliminates the use of corrosive acids, because FDCA is an effective catalyst for fructose dehydration, leading to improved economic and environmental impact of the process. Our techno-economic model indicates that the overall process is economically competitive with current terephthalic acid processes.